2016
DOI: 10.1080/0142159x.2016.1181730
|View full text |Cite
|
Sign up to set email alerts
|

The multiple mini-interviews as a predictor of peer evaluations during clinical training in medical school

Abstract: The study provides important evidence for the validity of the MMI. Additional studies are required to reevaluate the predicted validity of the MMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…They also found that IQ was negatively associated with belief in the importance of soft skills, leading them to suggest that soft skills may be used by less academically gifted students to compensate for their comparative lack of cognitive skills. Several medical schools in America have also commenced using multiple mini-interviews to assess the non-cognitive skills of applicants (Hadad et al , 2016). However, these interviews require trained examiners, and are conducted in person, making them impractical tools for larger surveys (Kulasegaram et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They also found that IQ was negatively associated with belief in the importance of soft skills, leading them to suggest that soft skills may be used by less academically gifted students to compensate for their comparative lack of cognitive skills. Several medical schools in America have also commenced using multiple mini-interviews to assess the non-cognitive skills of applicants (Hadad et al , 2016). However, these interviews require trained examiners, and are conducted in person, making them impractical tools for larger surveys (Kulasegaram et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Important evidence for the validity of the MMIs is provided by demonstrating that MMI scores are related to peer assessment conducted four years later. The scores of two MMIs (MOR and MIRKAM) were moderately correlated with the peer assessment done during clinical studies in medical school 44. Empathy, medical knowledge, teamwork, ability to cope with pressure and communications skills were among the domains identified for peer evaluation.…”
Section: Utility Of MMImentioning
confidence: 91%
“…To improve inter-rater reliability, researchers have recommended that programs focus on training of interviewers to use the MMIs in a standardized manner as well as training of interviewers to reduce the impact of bias in ratings (Axelson & Ferguson, 2012; Eva et al., 2018). Studies on the predictive validity of MMIs have found that MMI scores correlate reasonably well with results of performance-based clinical examinations (Eva et al., 2004a), licensing examinations (Eva et al., 2012; Reiter, Eva, Rosenfeld, & Norman, 2007), evaluations by supervisors during clinical placements (Reiter et al., 2007), and evaluations by peers during clinical placements (Hadad et al., 2016).…”
Section: Introductionmentioning
confidence: 99%